Investigation and Molecular Detection of Lumpy Skin Disease during an Outbreak in Cattle in the State of Tripura, India - Majumder, Saurabh; Chakraborty, Sandip; Paul, Avishek; Debnath, Apurba; Roy, Parimal (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during August, 2023 at the Department of Veterinary Microbiology, College of Veterinary Sciences and Animal Husbandry, Agartala, Tripura, India to establish the cause of a suspected lumpy skin disease outbreak in the cattle population at different villages of the Khowai district of Tripura. Lumpy skin disease is a contagious viral disease of cattle caused by lumpy skin disease virus, of the genus Capripoxvirus and family Poxviridae. The disease spreads mainly via biting insects and is characterized by fever, anorexia, enlarged lymph nodes, and development of firm, round skin nodules. It causes significant economic losses due to reduced milk yield, weight loss, production of inferior quality hides, and mortality in cattle. Tripura is a state located in the northeastern part of India with a 0.735 million cattle population. Animal husbandry is a major mode of income for a substantial part of the rural population, mainly marginal farmers. A large number of animals were affected. The disease was characterized by fever, anorexia, and the development of skin nodules that begin as firm, raised lumps ranging from a few millimeters to several centimeters in diameter, mostly in the neck, ears, limbs, and perineal regions. Over time, some of these nodules underwent necrosis and ulcerated, leading to secondary bacterial infections. In calves, the disease was severe and often fatal. The outbreak of the disease caused significant economic losses to the farmers. As per the clinico-pathological analysis and molecular detection method using samples collected from affected cattle, the disease was confirmed to be LSD.